A novel active equalization topology for series-connected lithium-ion battery packs - Ding, Xiaofeng; Zhang, Donghuai; Cheng, Jiawei; Wang, Binbin; Chai, Yameng; Zhao, Zhihui; Xiong, Rui; Luk, Patrick Chi-Kwong (IEEE, 2020)
A novel nondissipative two-stage equalization circuit topology based on the traditional buck-boost circuit is proposed to achieve balancing of series-connected lithium-ion battery packs with higher efficiency and less cost, considering the background on international energy issues and the development trend of battery balancing. The proposed topology achieves high efficient balancing of lithium-ion battery packs without adding additional devices. Detailed illustration of the presented topology, the operation principles and control approaches are described with visualized figures in this article. Then, under the condition of accurate modeling of the lithium-ion battery, relying on the experimental data, the simulation block is built based on MATLAB. Furthermore, the prototype of the proposed topology was designed and manufactured. The effectiveness of the proposed topology is verified by both the simulation and experiment.
Keywords: Balancing time; Lithium-ion battery model; Active equalization; Buck-Boost topology